Fermentación de subproductos protein-quitinosos (desechos de camarón) por Bacillus thuringiensis, para la producción de proteasa extracelular y cristales insecticidas - Rojas Avelizapa, Luz Irene (Universidad Autónoma Metropolitana, 1999)
La presente tesis forma parte de una línea de investigación tendiente a aprovechar los desechos de camarón por vía microbiana, utilizando a Bacillus thringiensis para la producción de proteasas, quitinasas, cristales insecticidas y un remanente sólido útil para la obtención de quitina y quitosana. Sin embargo, por la amplitud y complejidad que presenta una investigación de tal envergadura, el presente estudio aborda sólo los tres aspectos siguientes: i). La selección y caracterización de una cepa de Bacillus thringiensis, capaz de crecer en un medio conteniendo como Único ingrediente desechos secos y molidos de camarón, suspendidos en agua de suministro, para producir proteasas, quitinasas y cristales bioinsecticidas. ii). El estudio de materia prima y de algunas variables fisico-químicas que influyen en la producción de la proteasa a escala de matraz y fermentador, y iii). La caracterización parcial de la proteasa a nivel de extracto crudo. La selección en su fase primaria se llevó a cabo con 152 cepas de B. thuringzensis, sembrándolas en placas con medios ólidos específicos, para evaluar la producción de caseinasas y quitinasas extracelulares, por el tamano y el aspecto de los halos de hidrólisis en torno alas colonias de cada cepa. También se evaluó la producción de queratinasa extracelular (otro tipo de proteasa), sembrando las bacterias en un medio con lana tenida con azul brillante de remazol, cuya hidrólisis es evaluada por el incremento en la absorbancia a 585 nm. De este estudio resultaron ocho cepas cristalíferas, con un adecuado balance en la producción de caseinasas, queratinasas y quitinasas. La selección secundaria consistió en cultivar las ocho cepas promisorias, en un medio líquido conteniendo carapacho molido de camarón al 2% en agua de suministro, para hacer estudios cinéticos de la producción de proteasas. Cabe mencionar que en las fases primaria y secundaria de la selección se utilizaron también cepas patrón como Bt-149 especialmente proteolítica; Serratia marcescens W, muy proteo-quitinolítica, así como Bt-HD-1 y Bt-HD-73 usadas como referencia debido a su alta capacidad bioinsecticida. Al final quedaron sólo las cepas Bt-103 y Bt-112 para abordar una selección terciaria, en base a la capacidad insecticida de sus cristales purificados; aunque se hicieron estudios complementarios sobre la caracterización de ambas cepas. Los resultados obtenidos después de realizar bioensayos contra insectos modelo, abarcando dípteros, coleópteros y lepidópteros, mostraron que Bt-112 era moderadamente tóxica hacia el lepidóptero Manduca sexta, el gusano del tabaco, y por lo mismo se adoptó como cepa de trabajo para continuar la investigación. Cabe destacar que' Bt-112 posee cristales bipiramidales asociados a inclusiones cuboidales y esféricas, con proteínas cry de 65-70 y 130 kDa, semejantes a las encontradas en la cepa patrón internacional HD-1, aunque su perfil plasmídico (5.8, 7, 8.7 y 34 h4Da) es muy diferente. Además, la serotipificación mostró que Bt-112 pertenece a la variedad tohuorthi, en tanto que HD-1 corresponde a la variedad kurstak. Por su parte la cepa Bt-103 pertenece al serovar. finitimus, sus cristales pleomorficos están fbertemente asociados a la espora, y posee plásmidos de 47 y 80 MDa. En suma, aún cuando sólo Bt-112 he insecticida, ambas cepas resultaron muy interesantes, sobre todo en cuanto a su perfil plasmídico, el cual no ha sido reportado en ninguna otra cepa. Por otro lado, la morfología de los cristales de la cepa Bt-103 también resultó ser novedosa. Tanto Bt-112 como Bt- 103, heron tipificadas y conservadas en la colección del Instituto Pasteur, Francia, que es el centro de acopio y referencia de cepas de B. thuringzemis más importante a nivel internacional. En cuanto a los estudios para mejorar la producción de la proteasa extracelular de Bt112, en cultivo sumergido a escala de matraz, éstos se iniciaron relacionando análisis bromatológicos de la materia prima, con su capacidad para propiciar la síntesis de la enzima. De este modo se encontró que el contenido proteico actúa favorablemente, no así el contenido de grasas, de sal y de amonio. go se demostró haciendo estudios cinéticos, que la producción de proteasa alcanza un máximo (374 UP/ml) a 3 1"C, empleando el sustrato al 2%, suspendido en agua de suministro, con una agitación de 180 rpm y sin ningún ajuste en el pH inicial del medio (alrededor de 8.8), al cabo de 32 h de incubación. Al intentar aumentar los rendimientos llevando el proceso a escala de fermentador de laboratorio (New-Brunswick Bioflo m, 4 l), se encontró que utilizando las condiciones óptimas de los experimentos en matraz, aún con un mejor control y aireación (0.5 wm y 375 rpm), no se mejoró la producción de la enzima (350 UP/ml), aún cuando se redujo el tiempo de máxima producción de 32 a 22 h de incubación Tampoco se logró elevar la concentración enzimática en el caldo, al mantener constante el pH del medio a 7, o al aumentar la agitación y la aireación. Bajo estas condiciones se propició la solubilización de las proteínas presentes en el sustrato y con ello la formación de espuma. Esto obligó a la adición de antiespumante, el cual pareció tener un efecto dual, tanto sobre el microorganismo como sobre la proteasa ya presente en el medio, afectando drásticamente el rendimiento de la proteasa. Cabe destacar que los cristales insecticidas de Bt-112 se produjeron satisfactoriamente en el medio con carapacho de camarón a partir de las 24 h de incubación, tanto a nivel de matraz como de fermentador. Así mismo se produjeron modestas cantidades de quitinasa. Esto se debe a que en general, todas las cepas de B. thuringiensis estudiadas son poco quitinolíticas. En cuanto a la caracterización parcial de la proteasa extracelular de Bt-112, en forma de extracto crudo, puede destacarse que es una tiol-proteasa, sensible a los agentes quelantes, la cual mostró su máxima actividad a pH 8 y 45°C. Su vida media de anaquel en refrigeración (5OC) es de 1.9 meses, y de 2.7 meses en congelación (-1 5OC). El CaClz favoreció la acción de la proteasa, y según la concentración de la sal puede darse un efecto de activación, o de mayor estabilización al efecto de la temperatura. Los detergentes neutros favorecen la acción enzimática, lo contrario ocurre con la urea y los detergentes aniónicos. Finalmente, los experimentos de electroforesis ugieren la presencia de una sola proteasa de un peso molecular aproximado de 36 kDa. En suma, pueden considerarse como contribuciones del presente trabajo: La propuesta de uso novedoso para los desechos de camarón, como sustrato de fermentación para la producción de proteasa ycristales bioinsecticidas. Ampliar los usos biotecnológicos para B. thuringzensis; ya que hasta ahora su empleo se ha restringido a la producción de cristales. Las exoenzimas de B. thringiemis en lo general han sido poco estudiadas. En este trabajo se describen algunas características de la proteasa alcalina de esta bacteria.; This research involved three different aspects: i).- Selection and characterization of a Bacillus thringiensis strain to produce extracellular proteases and chitinases as well as intracellular protein crystals with bioinsecticide activity. These strains were selected for their ability to grow in a medium containing dried and milled shrimp wastes, as the sole ingredient in tap water. ii).- Chemical analysis of raw materials were performed, in order to study the influence of its components on the protease production. The influence of some enviromental physico-chemical variables, both at flask and fermentator levels, on protease production were also studied iii).- Partial characterization of the crude protease extract. In an initial screening, 152 strains of B. thuringensis were inoculated by striking on solid specific media, in order to evaluate the production of extracellular caseinase and chitinase. This evaluation was carried out according to the size and aspect of the hydrolysis haloes, surrounding the colonies of each particular strain. In addition, the production of keratinase, another type of proteolytic enzyme was also evaluated. In this case all strains were cultured in a medium with 0.4% milled wool, previously stained with remazol brilliant blue, and production of the enzyme was followed by digestion of the solid substrate, that release a soluble dye into the medium, its absorbance was read at 585 m. From this part, eight crystalliferous strains were chosen based on their approriate enzymatic balance. A second selection consisted of culturing the eight chosen strains in a liquid medium containing only 0.2% milled shrimp waste in fresh water, to study their protease production kinetics during a total study time of 45 h. In these two experiments, some strains were included as references, these strains were Serratia marcescens WF due to its very high proteolytic and chitinolytic extracellular activities; Bt-149 for its high proteolytic activity, and Bt-HD-1 as well as Bt-HD-73 due to their production of entomocidal crystals. Mer the secondary selection, only Bt-103 and Bt-112 strains were considered for hrther studies. In a third selection, bioassays were carried out with previously purified crystals of Bt-103 and Bt-112, against coleopterous, lepidopterous and dipterous plague-model insects. Additionally, a complementary characterization of both strains was also done. The results obtained showed that Bt-112 was moderately toxic against Münduca sexta larvae, a lepidopterous known as tobacco worm, whereas Bt-103 was not toxic against any of the tested insects. Therefore Bt-112 was chosen to continue the experiments. However it is important to note that Bt-112 produced bipyramidal crystals associated to semicuboidal and spherical inclusions. The electrophoretic pattern of their cry-proteins showed a mayor band around 130 kDa, and two minor components between 65 and 70 Da. These data were similar to these found in HD-1 protein crystal composition. However their plasmid electrophoretic profiles were different. Bt-112 had four plasmids of 5.8, 7, 8.7 and 34 MDa. In additon, fbrther characterization of Bt-112 indicated that it corresponded to serovar. tohuorthi, whilst it is know that HD-1 belongs to serovar. kurstaki. With respect to Bt-103, it corresponded to serovar.finitimus, its crystals are pleomorphic in shape, strongly associated to spores. In conclusion although only Bt-112 was entomocidal, both strains resulted interesting because of their peculiar plasmids profiles, the morphology of their crystals (particularly Bt103) and their biotechnological posibilities, and therefore they were sent to the Pasteur Institute of France for their sero-characterization and storage. This Institution is the more important international center for reference and storing of B. thuringensis strains in the world. With regard to optimization of the production of extracellular protease of Bt-112 in submerged cultures at evaluatory scale, an initial comparison of the chemical composition of raw materials (different shrimp-waste meals) and their efficiency to trigger the enzyme synthesis was carried out. It was found that high protein content promoted protease production, but salt, fats and ammonia did not. Studies on enzyme kinetics production showed that the optimal conditions were: 31"C, shaking at 130 rev/min, and 2% substrate concentration in tap water. These results were not improved by using a conventional mineral medium, or by changing the initial pH of the medium to 7, which normally is 8.8. Under these optimal conditions, the enzyme concentration reached 350 protease unitdml, after 32 h of incubation. Subsequent experiments in 4 1 fermentator (New Brunswick Bioflo 111), under the previously mentioned optimal conditions, and aireation-shaking of 0.5 wm - 375 rev/min, demonstrated that no more enzyme concentration was obtained. However, the time required to produce 350 UP/ml was reduced fiom 32 h to 22. Not more enzyme concentration was obtained by maintaining constant the pH of the medium to 7, nor by rising the aireationshaking. Conversely, under these conditions solubility of proteins associated to the substrate was increased, making ecesary of antifoaming substances during fermentation. Antifoaming agents affected both bacterial integrity as well as protease molecules already present in the culture, causing a fall in protease yield. It is important to emphasize that there was a considerable production of entomocidal crystals, with Bt-112 grown in the shrimp-waste medium, both in flask and in a fermentator experiments. Likewise, in both levels a small amount of chitinase was produced. This could be explained by the fact that , of the initial 152 strains studied B. thuringrensis strains, all them very little chitinolytic activity as compared to S. marcescens WF. The last experiments consisted on partial characterization of Bt-112 crude protease. They suggested the presence of a single enzyme, of 36 kDa. It was a thiol-dependent protease inhibited by chelating agents such as EDTA. Its highest activity occured at pH 8 and 45OC, and had a half life of 1.9 months at 5°C or 2.7 months at -15°C. The protease was activated and stabilized by the addition of CaCl2. Neutral detergents can also favored the enzymatic activity, whereas urea and anionic detergents could have an opposite effect. i) ii) iii) Finally as contributions of the present research can be considered: The proposal of a new use for shrimp refuses as fermentation substrate, for producing extracellular protease and bioinsecticide crystals. The proposal to extend the biotechnological application of B. thringrensis as an exoenzyme producer. This bacterium has been used only to produce bioinsecticides. In spite of B. thringrensis produces several extracellular enzymes that could have practical applications, the studies about these enzymes are very scarce. In this research several characteristics of its alcaline protease are describe.